Structural Evidence for a Reinforcing Response and Retention of Hydration During Confinement of Cartilage Lipids - Mears, Laura L. E.; Abbott, Stephen B.; Barker, Robert D.; de Vos, Wiebe M.; Prescott, Stuart W.; Richardson, Robert M. (Frontiers in Physics, 2021)
Lipids have an important role in the complex lubrication of articulating joints, however changes in lipid phase behavior that occur owing to mechanical confinement are not well understood. Here, a surface force-type apparatus has been combined with neutron reflectometry to measure confinement-induced changes in the structure of lipids, the major surface-active component of the lubricant in articulating joints. The same incompressible state was accessed under low uniaxial stress (1 bar), irrespective of whether the lipids had started out unconfined above or below the Lα phase transition, and irrespective of whether they were fully or partially hydrated. In this incompressible state, the lipid component had thickened indicating extension and rearrangement of the lipid chains in response to the applied stress. The small amount of water remaining between each lipid bilayer was found to be similar for all chain lengths and starting phases. This represents the first structural evidence of the tightly bound water layer at the headgroups, which is required for hydration lubrication under load.